2010
DOI: 10.4141/cjss09062
|View full text |Cite
|
Sign up to set email alerts
|

Soil characteristics in relation to groundwater for selected Dark Brown Chernozems in southern Alberta

Abstract: Miller, J. J. and Chanasyk, D. S. 2010. Soil characteristics in relation to groundwater for selected Dark Brown Chernozems in southern Alberta. Can. J. Soil Sci. 90: 597Á610. Limited information exists on soil characteristics in relation to groundwater for undulating morainal landscapes of the Dark Brown soil zone in western Canada. A 4-yr (1985Á1988) field study was conducted in southern Alberta to investigate these relationships for selected Dark Brown Chernozems. Soil morphology, physical and chemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…These unsaturated fluxes were also consistent with saturated fluxes ( (6.23 )10 (10 m s (1 ) that were measured between 25 and 35 m depth at this same site (Miller and Chanasyk 2010). Zebarth and de Jong (1989) Daily water flux directions at the lower slope position in 1985 were upward from May 16 to Jun.…”
Section: Precipitation and Evaporationsupporting
confidence: 68%
See 4 more Smart Citations
“…These unsaturated fluxes were also consistent with saturated fluxes ( (6.23 )10 (10 m s (1 ) that were measured between 25 and 35 m depth at this same site (Miller and Chanasyk 2010). Zebarth and de Jong (1989) Daily water flux directions at the lower slope position in 1985 were upward from May 16 to Jun.…”
Section: Precipitation and Evaporationsupporting
confidence: 68%
“…Parameters estimated from soil water characteristic curves using RETC model (van Gehnucten et al 1991). The exception was saturated hydraulic conductivity, K s , which was determined directly on soil cores in the laboratory using constant head method (Miller et al 2010), and with this site being identified as a ''local recharge'' area for saline seepage at lower slope positions (Miller 1989).…”
Section: Precipitation and Evaporationmentioning
confidence: 99%
See 3 more Smart Citations